2018
DOI: 10.1016/j.nucmedbio.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Re(CO) 3 ([ 18 F]FEDA), a novel 18 F PET renal tracer: Radiosynthesis and preclinical evaluation

Abstract: F-1 exhibited a high specificity for the kidney, rapid renal excretion comparable to that of I-OIH and high in vivo radiochemical stability. Not only isF-1 a promising PET renal tracer, but it provides a route to the development of a pair of analogous F/Tc renal imaging agents with almost identical structures and comparable pharmacokinetic properties. These promising in vivo results warrant subsequent evaluation in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…The PET images were first co-registered to the CT images. Partial regions of interest were drawn on the CT images of a selection of mouse organs: brain, heart, lungs, liver, muscle, large intestine, and bone marrow to obtain the activity concentration in 17 measured time-points after injection (0, 5,10,15,20,25,30,35,40,45,50,55,60,65,70,75, 80 and 85 min). Whole-organ contours were drawn to measure the activity in the kidneys and bladder of the mice.…”
Section: Dosimetry Analysismentioning
confidence: 99%
“…The PET images were first co-registered to the CT images. Partial regions of interest were drawn on the CT images of a selection of mouse organs: brain, heart, lungs, liver, muscle, large intestine, and bone marrow to obtain the activity concentration in 17 measured time-points after injection (0, 5,10,15,20,25,30,35,40,45,50,55,60,65,70,75, 80 and 85 min). Whole-organ contours were drawn to measure the activity in the kidneys and bladder of the mice.…”
Section: Dosimetry Analysismentioning
confidence: 99%
“…However, novel PET radiotracers, such as [ 68 Ga]EDTA, [ 18 F]FDS and Re(CO) 3 ([ 18 F]FEDA), may have superior pharmacokinetic profiles, mainly due to low plasma protein binding and high metabolic stability (Fig. 1) [6, 14, 17].
Fig.
…”
Section: Comparison Of Pet Single-photon Planar Imaging and Spect Inmentioning
confidence: 99%
“…Based on these encouraging results, the authors demonstrated similar findings by developing an efficient, one-step radiosynthesis of an 18 F-Re-tricarbonyl PET tracer, namely Re(CO) 3 ([ 18 F]FEDA). Re(CO) 3 ([ 18 F]FEDA) shows high renal specificity, high in vitro and in vivo stability and rapid renal excretion, which are comparable to those of its analogue [ 99m Tc](CO) 3 (FEDA) [17]. The pharmacokinetic properties of Re(CO) 3 ([ 18 F]FEDA) are also comparable to those of [ 131 I]OIH, which is considered the reference standard for ERPF measurement [17, 42].…”
Section: F-labelled Radiotracers For Renal Function Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging of specific molecular targets, such as CD206 within the glomerulus and the organic anion transporter 1 of proximal tubules (45,46), represents a complementary strategy for the noninvasive measurement of renal function. Both targets are energy-dependent transporters of physiologically significant molecules at 2 critical cell types that serve different functions within the kidney.…”
Section: Optimization Of the Molecular Imaging Agentmentioning
confidence: 99%